2006
DOI: 10.1139/f05-230
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different ligands on the bioaccumulation and subsequent depuration of dietary Cu and Zn in juvenile rainbow trout (Oncorhynchus mykiss)

Abstract: The effects of different ligands on the bioavailability of dietary copper (Cu) and zinc (Zn) to fish have not been thoroughly investigated. We therefore exposed juvenile rainbow trout (Oncorhynchus mykiss; ~200 mg body weight) to control food or to food supplemented with different Cu (~400 µg·g–1 food) or Zn (~1000 µg·g–1 food) compounds. Tissue metal accumulation was compared among groups. Fish fed CuO showed no differences in tissue Cu concentrations relative to control fish, suggesting that Cu was not readi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 28 publications
3
9
0
Order By: Relevance
“…Similarly, the threshold concentrations for dietborne Cu toxicity also differ among species such as channel catfish Ictalurus punctatus (Rafinesque) (Gatlin & Wilson, 1986), Atlantic salmon (Berntssen et al, 1999b) and rainbow trout Oncorhynchus mykiss (Walbaum) (Lanno et al, 1985a(Lanno et al, , b, 1987Julshamn et al, 1988). Considerably higher dietary copper levels (c. 400 mg kg À1 ), resulting in substantial increases in liver, gut tissue and whole-body Cu concentrations, did not exhibit detrimental effect on rainbow trout growth (Kjoss et al, 2006). Over 730 mg Cu kg À1 diet, however, reduced growth and induced an aversion to food (Lanno et al, 1985b).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Similarly, the threshold concentrations for dietborne Cu toxicity also differ among species such as channel catfish Ictalurus punctatus (Rafinesque) (Gatlin & Wilson, 1986), Atlantic salmon (Berntssen et al, 1999b) and rainbow trout Oncorhynchus mykiss (Walbaum) (Lanno et al, 1985a(Lanno et al, , b, 1987Julshamn et al, 1988). Considerably higher dietary copper levels (c. 400 mg kg À1 ), resulting in substantial increases in liver, gut tissue and whole-body Cu concentrations, did not exhibit detrimental effect on rainbow trout growth (Kjoss et al, 2006). Over 730 mg Cu kg À1 diet, however, reduced growth and induced an aversion to food (Lanno et al, 1985b).…”
Section: Discussionmentioning
confidence: 97%
“…Considerably higher dietary copper levels ( c . 400 mg kg −1 ), resulting in substantial increases in liver, gut tissue and whole‐body Cu concentrations, did not exhibit detrimental effect on rainbow trout growth (Kjoss et al , 2006). Over 730 mg Cu kg −1 diet, however, reduced growth and induced an aversion to food (Lanno et al , 1985 b ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although TTF values >1 generally indicate the potential for biomagnification, Zn is not generally expected to biomagnify in piscivorous fish because, as in many other marine organisms, Zn concentrations in fish are regulated (Goodyear & Boyd 1972, Roch et al 1982. Zn AEs in marine animals vary with Zn concentration in the diet (Wang et al 1996a) such that Zn tissue concentrations remain fairly constant among fish with increasing trophic level and with increasing fish size (Amiard et al 1987, Kjoss et al 2006. However, several studies have reported ele-31 Mar Ecol Prog Ser 367: 23-33, 2008 vated Zn concentrations in fish, and there is evidence of Zn biomagnification in some food chains both in the laboratory and in the field (Zhang & Wang 2007).…”
Section: Growth and Metal Accumulation Over Time Inmentioning
confidence: 99%
“…In this study, we illustrated combined approaches to investigate the Cu and Zn interaction with metal clearance from the water, which may be an effective and notable route to determine metal interactions on uptake and distribution in different mussel tissues. Cu and Zn are essential metals to the normal metabolism of mussels and their importance of the diet as the prime source has long been recognized by aqua-cultural nutritionists [20]. The gigantic filterfeeder mussel, C. plicata, one of the most important freshwater pearl mussels, is widespread and abundant in China and was selected for testing under laboratory conditions.…”
Section: Introductionmentioning
confidence: 99%